EFEKTIVITAS MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Jahring Jahring; Marniati Marniati (Jurnal Karya Pendidikan Matematika, 2020)
This research aims to determine the effectiveness of learning model inside outside circle on mathematics learning outcomes of students of grade IX SMP Negeri 3 Watubangga. This research is a research experiment (quasi experimental design) with the design of non-equivalent control group design. The population is all students of grade IX SMP Negeri 3 Watubangga as much as 52 people. Sampling with a totally sampling technique obtained the IXA class as the experimental class and the IXB class as the control class. The hypothesis test indicates that at the level of the significance α = 0.05, the value of tcount = 2,048 > ttable = 1,676. That means that H0 rejected and H1 accepted. So that the inside outside circle learning model is more effective to mathematics learning outcomes of students in grade IX SMP Negeri 3 Watubangga compared with conventional learning.